Social, economic, and environmental impacts between sustainable financial systems and financial markets - Ziolo, Magdalena, 1976- (Practice, progress, and proficiency in sustainability (PPPS) book series., 2020)
"This book explores sustainable financial systems, sustainable finance, blended finance, ESG risk, and individual and institutional motivations of financial managers in the sustainability. It also examines the link between finance, financial systems, financial markets, and externalities"--